(untitled) (Annals of Bangladesh Agriculture, 2021)
Two experiments were carried out to evaluate the effects of addition of net piece substrates in cages for nursery rearing of freshwater prawn, Macrobrachium rosenbergii post-larvae. In the first experiment, net piece substrates were added with an arrangement to increase the surface area of nursery cages to 50% and 75% and compared with cages without any substrate (control). In the second experiment, maintaining surface area increment at 75% in all cages, the net piece substrates were arranged in three different orientations of horizontal, vertical, and 45o angle sloping. Experiments were conducted in a pond of Faculty of Fisheries, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, Bangladesh for a period of 45 days in June –August of 2015 and 2016. A completely randomized design was followed to assign the treatments with three replications. The 75% area increment group showed significantly higher (P < 0.05) growth (1.02 ± 0.09 g) and survival rate (79.43 ± 1.63%), compared to 50% area increment (0.96 ± 0.05 g and 75.03 ± 2.45%) and control group (0.79 ± 0.06 g and 66.66 ± 3.57%). The vertically oriented substrate group showed significantly lower growth 0.95 ± 0.04 g) and survival (76.33 ± 1.15%), compared to the horizontal (1.06 ± 0.05 g and 77.12 ± 1.20%) and sloping (1.16 ± 0.10 g and 79.33 ± 0.57 %) substrate group. However, there were no differences between horizontal and sloping substrate groups regarding final length, final weight, specific growth rate (SGR), and survival rate except food conversion ratio (FCR). The overall results suggested that modification of net cage nursery structure of M. rosenbergii might have significant effects on growth and survival of post-larvae by the manipulation of their behaviour in culture system. Ann. Bangladesh Agric. (2020) 24(2) : 95-106